2016
DOI: 10.4067/s0717-95022016000400026
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Measurement of the Morphometry and Angles of the Anterior Clinoid Process (ACP) for Aneurysm Surgery

Abstract: CELIKOGLU, E.; IS, M.; CETINER KALE, A. & TORUM EROGLU, B.Pre-operative measurement of the morphometry and angles of the anterior clinoid process (ACP) for aneurysm surgery. Int. J. Morphol., 34(4):1333Morphol., 34(4): -1338Morphol., 34(4): , 2016. SUMMARY:The anterior clinoid process (ACP) is proximal to vital structures, such as the optic nerve, internal carotid artery and ophthalmic artery; therefore, study of its anatomy is important in guiding and defining surgery. We studied the anatomical structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 22 publications
5
20
2
Order By: Relevance
“…9,12,14,18,[25][26][27][28] Anatomical features of ACP and OS may affect surgical approach selection, patient positioning, and intraoperative surgical orientation. 18,23,25,29 For instance, considering the length, width, and angle of ACP, Cecen et al 23 classified its morphology as 3 different configurations: the long, narrow, and narrow-angled type (43 ACPs, 17.8%); the short, wide, and wideangled type (40 ACPs, 16.5%); and the other types (159 ACPs, 65.7%). They reported that the long, narrow, and narrow-angled ACP might call for a more complicated operating procedure, while the short, wide, and wide-angled ACP for an easier intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12,14,18,[25][26][27][28] Anatomical features of ACP and OS may affect surgical approach selection, patient positioning, and intraoperative surgical orientation. 18,23,25,29 For instance, considering the length, width, and angle of ACP, Cecen et al 23 classified its morphology as 3 different configurations: the long, narrow, and narrow-angled type (43 ACPs, 17.8%); the short, wide, and wideangled type (40 ACPs, 16.5%); and the other types (159 ACPs, 65.7%). They reported that the long, narrow, and narrow-angled ACP might call for a more complicated operating procedure, while the short, wide, and wide-angled ACP for an easier intervention.…”
Section: Discussionmentioning
confidence: 99%
“…and with well quality CBCT scans. The exclusion criteria of the study were as follows: subjects aged under 18 y; CBCT images with artifact and distortion in the examination area, taking into account previous studies,20,23–25 the following parameters were determined (Fig. 1): Considering the classification of Lee et al,20 OS location relative to ACP was identified as six types: Type A: anterior to ACP root, Type B: anterior 1/5 of ACP, Type C: anterior 2/5 of ACP, Type D: anterior 3/5 of ACP, Type E: anterior 4/5 of ACP, and Type F: posterior 1/5 of ACP. It was determined whether there was ACP pneumatization.…”
Section: Methodsmentioning
confidence: 99%
“…The length and width of ACP influence its type which influences the surgical techniques applied during anterior clinoidectomies (Cecen et al, 2016). Based on our modification of the criteria by Cecen et al, (2016), most of the ACP in our population were type IIIb (long and wide). This is comparable to the findings of Cecen et al, 2016 on a Brazilian population in which type III ACPs in general were the commonest (65.7%).…”
Section: 8%mentioning
confidence: 93%
“…The dimensions are used to determine the types of ACP. The types influence the choice of surgical technique employed during anterior clinoidectomy (Cecen et al, 2016). There is however paucity of data in the African populations and lacking all together among Kenyans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation